THE ROLE OF MADRASA CULTURE AND FAMILY SUPPORT IN INCREASING RELIGIOSITY IN STUDENTS AT YOGYAKARTA STATE MADRASAH ALIYAH - Abdul Hopid; Sutipyo Ru'iya; Abdulrahman Sama alee (STAI Ma'had Aly Al-Hikam Malang, 2026)
Religious students are the main goal of education in madrasas, as Islamic-based general educational institutions. The aim of this study is to measure the role of madrasa culture and family support on the Islamic religiosity of students at Madrasah Aliyah Yogyakarta. This research is set at Madrasah Aliyah as an Islamic-based general educational institution in the areas around Yogyakarta, namely Bantul Regency, Yogyakarta City, and Sleman Regency. Respondents were randomly selected from grade 2 students, because they had experienced madrasa life for at least one year. The number of respondents was 325 people. Data collection used three questionnaires, including the madrasa culture questionnaire, family support, and Islamic religiosity. Data analysis used multivariate analysis using the SmartPLS 3.0 application to obtain more accurate results. The results of the study showed that family support significantly influenced Islamic religiosity by 22.8%, while madrasa culture significantly influenced Islamic religiosity by 72.6%. So it can be concluded that Islamic religiosity among students at Yogyakarta State Madrasah Aliyah increases along with increasing family support and madrasa culture. Keywords: family support; Islamic religiosity; madrasa culture. Abstrak Siswa yang religius merupakan tujuan utama dari pendidikan di madrasah, sebagai lembaga pendidikan umum berbasis Islam. Tujuan penelitian ini adalah untuk mengukur peran budaya madrasah dan dukungan keluarga terhadap religiusitas Islami siswa di Madrasah Aliyah Yogyakarta. Penelitian ini mengambil seting di Madrasah Aliyah sebagai lembaga pendidikan umum yang berbasis Islam di daerah sekitar Yogyakarta yaitu Kabupaten Bantul, Kota Madya Yogyakarta, dan Kabupaten Sleman. Penentuan responden secara acak pada siswa kelas 2, karena mereka sudah mengalami kehidupan madrasah minimal satu tahun. Jumlah responden 325 orang. Pengumpulan data menggunakan tiga kuesioner, antara lain kuesioner budaya madrasa, dukungan keluarga, dan religiusitas Islami. Analisis data menggunakan analisis multivariat menggunakan aplikasi SmartPLS 3.0 agar memperoleh hasil yang lebih akurat. Hasil penelitian menunjukkan bahwa dukungan keluarga berpengaruh terhadap religiusitas Islami secara signifikan sebesar 22,8%, sementara budaya madrasa berpengaruh terhadap religiusitas Islami secara signifikan sebesar 72,6%. Sehingga dapat disimpulkan bahwa religiusitas Islami pada siswa Madrasah Aliyah Negeri Yogyakarta meningkat seiring dengan meningkatnya dukungan keluarga dan budaya madrasa. Kata Kunci: budaya madrasah, dukungan keluarga, religiositas Islami.